2012
DOI: 10.1038/nphys2334
|View full text |Cite
|
Sign up to set email alerts
|

Experimental estimation of the dimension of classical and quantum systems

Abstract: Experimental observations are usually described using theoretical models that make assumptions about the dimensionality of the system under consideration. However, would it be possible to assess the dimension of a completely unknown system only from the results of measurements performed on it, without any extra assumption? The concept of a dimension witness 1-6 answers this question, as it allows bounding the dimension of an unknown system only from measurement statistics. Here, we report on the experimental d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
119
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(126 citation statements)
references
References 36 publications
(57 reference statements)
2
119
0
2
Order By: Relevance
“…This reveals that assessing high dimensions in a DI manner constitutes an experimental challenge, since it requires much higher control and accuracy than previous experiments assessing dimensions in a DI manner [17,18]. This is the challenge that we address here.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…This reveals that assessing high dimensions in a DI manner constitutes an experimental challenge, since it requires much higher control and accuracy than previous experiments assessing dimensions in a DI manner [17,18]. This is the challenge that we address here.…”
mentioning
confidence: 75%
“…So far, DI DWs have only been used to experimentally certify the generation of classical and quantum systems of dimension 2 and 3 [17,18]. However, realistic quantum information processing applications demand quantum systems of much higher dimensions.…”
mentioning
confidence: 99%
“…These results are not only interesting from the fundamental point of view but also play a role in quantum information processing. Besides allowing for experimental tests of the physical dimension [1], which might be considered as a resource, these investigations allow to constrain the correlations that are achievable when the setting limits the underlying dimension of the physical systems used in a protocol. These scenarios are know as semi-device-independent quantum information processing: no assumption is made on the working of the devices nor on the physical systems used except for its dimension.…”
Section: Introductionmentioning
confidence: 99%
“…To estimate the lower bound of the dimensions of a physical system, quantum dimension witness has been proposed and experimentally realized [6][7][8][9] , which has important applications in the semi-device-independent quantum key distribution and quantum random number generation [10][11][12][13][14][15] . Until now, it has been demonstrated that two-observer classical dimension witness violation can be achieved with the Bell inequality test, quantum random access code test, and determinant value test respectively [16][17][18] , but whether the multi-observer classical dimension witness violation can be obtained or not is still an open question.…”
mentioning
confidence: 99%